1998
DOI: 10.1017/s0144686x98006916
|View full text |Cite
|
Sign up to set email alerts
|

Resisting the ‘mask’ of old age?: the social meaning of lay health beliefs in later life

Abstract: While the substantial literature on lay health beliefs gives some consideration to older people's conceptions of health and illness, it is material which has yet to be examined from the perspective of postmodern theory. This article, therefore, critically examines the value of using ideas from postmodernism in such a context and focuses on data obtained from a series of in-depth interviews with a sample of fifteen older people. During the interviews they were asked to talk about themselves in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…). Fourth, the perceived negativistic attitudes of healthcare professionals, potentially denying treatment because of the patient's age, may provide reasons for older individuals to resist a perceived negative portrayal of old age in modern medicine and wider society (Conway and Hockey , Higashi et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Fourth, the perceived negativistic attitudes of healthcare professionals, potentially denying treatment because of the patient's age, may provide reasons for older individuals to resist a perceived negative portrayal of old age in modern medicine and wider society (Conway and Hockey , Higashi et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than alter her help-seeking behaviour as she said her doctor advised, Annie reported attending the emergency department 12 times for palpitations. Similarly, Arthur became increasingly certain of his doctor's negativistic attitude towards interventions for older patients and mentioned this repeatedly; by so doing he both cemented his original beliefs and resisted the negative attitude that he perceived healthcare professionals held towards older people (Conway andHockey 1998, Higashi et al 2012). In all the situations described above, those giving negative accounts of healthcare professionals also expressed their difficulty in adapting to what they believed to be their increasingly threatened independence.…”
Section: Not Receiving Medical Treatment Believed Necessarymentioning
confidence: 99%
“…The ideal of maintaining an active life while aging, despite illnesses or physical limitations, was prized by all the study participants, and to this end, they actively engaged in both biomedical and CAM healing strategies. The women took responsibility for and felt empowered by their management of health care treatments and providers—and explained that this management encouraged them to be more active and participatory in their health 21,22,27. Earlier studies in the gerontological literature characterize older patients as particularly unwilling to act independently of medical authority and exercise independent judgment 28,29.…”
Section: Discussionmentioning
confidence: 99%
“…He found that older patients were highly satisfied with and felt empowered by CAM treatments. Similarly, in a study of health beliefs in 15 older people, Conway and Hockey22 found that participants who reported using homeopathy contrasted the empowering experience of CAM with the paternalistic and patronizing experiences of biomedicine. In interviews with 77 older adults, Kelner and Wellman23 showed that patients choose specific kinds of practitioners for particular problems, and some engage with a mixture of practitioners to treat a specific complaint.…”
Section: Introductionmentioning
confidence: 96%
“…It is clear that on the whole trial patients were more disabled than their day centre counterparts, but there was also a degree of overlap between the two populations suggesting an element of arbitrariness in referrals for treatment. Conway & Hockey (1998) highlight that health problems in older people are often attributed to age itself. An implication of this is that there may be a reluctance to see ailments associated with later life as treatable.…”
Section: Discussionmentioning
confidence: 99%